Understanding Fan Reactions to NFC Albums in the Shift Toward Sustainable Music Technology - Daphne Juwana; Devi Maudina Nabila; Zulfidar Akaha (COMMENTATE: Journal of Communication Management, 2026)
In response to growing environmental concerns, the music industry has introduced Near Field Communication (NFC) albums as a sustainable alternative to traditional physical albums. While these innovations aim to reduce material waste, their adoption raises questions about how fans engage with and perceive such formats in the context of fan culture and emotional connection. This study explores the perceptions of K-pop fans toward NFC albums, focusing on the interplay between sustainability, technology, and emotional experience. Using a qualitative research approach, data were collected through in-depth interviews with selected fans who have interacted with NFC albums. The study employs thematic analysis to examine the narratives fans attach to this shift, introducing 'affective sustainability' as an emerging conceptual interpretation of emotional and ethical negotiation in fandom consumption.